Konstruksi Konsep Budaya Risiko Islami dalam Manajemen Risiko Operasional Lembaga Keuangan Syariah - Gusti Oka Widana; Siti Handayaningsih (Jurnal Ilmiah Ekonomi Islam, 2025)
This research aims to construct the concept of Islamic Risk Culture (IRC) as a response to the limitations of the conventional Risk Culture (RC) model. Conventional RC is considered compliance-based and oriented toward materialism, which is inconsistent with Islamic ethics. This approach contradicts Islamic business ethics founded on the principles of Tauhid and deontology. The IRC is proposed as a new conceptual framework (novelty) for Sharia Financial Institutions (LKS). The IRC integrates conventional RC pillars (Tone at the Top, Accountability, and Incentives) with Sharia values (Amanah, Shiddiq, and Justice/Maslahah) This integration results in Islamic operational concepts: Ethical Islamic Leadership (Qudwah), Internal Hisbah, and a Fair Reward and Punishment System. Amanah (trustworthiness, integrity, and responsibility) and Shiddiq (honesty, truthfulness, and transparency) are positioned as the Core Values of IRC. The primary goal is to achieve Maslahah (public welfare) and eliminate the highest spiritual risk. The main implication of the IRC is the reinforcement of operational risk prevention stemming from human failures (human errors and misconduct). The value of Amanah (integrity and responsibility) functions as an ex-ante behavioral control that prevents negligence or human errors at the First Line of Defense. Shiddiq (honesty and transparency) serves as the moral foundation for preventing behavioral deviations, such as fraud and creative accounting, by mandating the disclosure of factual and objective information. Ultimately, the IRC acts as an internal moral compass for every employee, consistently directing them toward honesty and responsibility.